The reliability analysis of Prickelâs writing self-efficacy scale in Indonesian context - Setyowati, Lestari (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2016)
This study is intended to describe the quality of writing self-efficacy scale when it was applied in foreign language context. The design used is Correlational analysis by using Cronbach Alpha statistical tool. The participants of the study were 55 students of English Education Study program of STKIP PGRI Pasuruan who joined Writing II course and who were randomly chosen to fill out the questionnaire. The data were collected from 10 to 11 September 2014. The result of the study shows that the reliability is r = .785, lower than the reliability claimed by the maker (r = .9249). The possible cause of the reliability difference is discussed as well as the recommendation for future researchers.